(untitled) (Communication & Society, 2011)
International relations changed substantially over the past twenty years, giving way to an international system that has questioned the basis on which claims. Such changes supported the expansion of the public diplomacy. The following article describes the dimensions and the elements of communication strategies in this field of study as well as the main challenges for its consolidation under the new foreign affairs umbrella.